Biomassa sebagai Transisi Energi Terhadap Potensi, Daya Saing Ekonomi, dan Dampak Emisi - Jusnita, Jusnita; Hidayatullah, Resky Gerhana; Fithry, Dwi Annisa (SURYA TEKNIKA, 2026)
Indonesia possesses abundant biomass resources with significant potential to support the transition toward a sustainable energy system. This study evaluates the energy potential of major biomass resources in Indonesia, including oil palm residues, rice residues, corn residues, livestock manure, sugarcane bagasse, municipal solid waste, and cassava residues. A combination of quantitative and qualitative approaches was employed using national statistical data, government reports, and scientific literature. Energy potential was estimated based on biomass availability, calorific value, conversion efficiency, and energy losses during utilization. The results show that biomass has the potential to generate 30.76 GW of energy, equivalent to 12.8% of Indonesia’s final energy consumption in 2023. Oil palm residues provide the largest contribution (13.34 GW), followed by rice residues (7.12 GW) and livestock manure (5.49 GW). Despite ongoing challenges related to fossil fuel dependence, greenhouse gas emissions, and deforestation, biomass offers a promising alternative energy source. Furthermore, the Gross External Damages (GED) analysis indicates that biomass is more economically competitive than fossil fuels when environmental costs are considered. These findings highlight the strategic role of biomass in supporting Indonesia’s sustainable energy transition, climate change mitigation, and societal welfare improvement.